The Influence of Service Delivery and Information Quality on Patient Satisfaction at Reksodiwiryo Hospital, Padang City - Dede Tri Wahyu Kotama; Dasman Lanin (Program Pascasarjana Universitas Negeri Makassar, 2023)
The purpose of this study is to determine or analyze the effect of service delivery and information quality on patient satisfaction at Reksodiwiryo Hospital, Padang City. In this study using a quantitative approach research method. The population in this study were people who had visited the Padang City Reksodiwiryo Hospital. Sampling in this study used the William G. Cochran formula, this was based on the fact that the samples in this study could not be identified, by using this formula a sample of 96 samples of patients was obtained. The sampling technique used is simple random sampling. Data were collected using questionnaires distributed to respondents with measurements using a Likert scale. In this study, all the data obtained will be analyzed using simple and multiple linear regression. Results a) service delivery affects patient satisfaction, b) information quality affects patient satisfaction, c) service delivery and information quality affects patient satisfaction.